Presence, Play, Difference: Derrida and His “Marginal” Theatrical Comments: Презенција, игра, разлика: Дерида и неговите „маргинални“ театарски коментари - Lužina, Jelena; Stoev, Goran (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jelena Lužina | Јелена Лужина Title (English): Presence, Play, Difference Title (Macedonian): Презенција, игра, разлика Translated by (Macedonian to English): Goran Stoev | Горан Стоев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 169-186 Page Count: 17 Citation (English): Jelena Lužina, “Presence, Play, Difference,” translated from the Macedonian by Goran Stoev, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 169-186. Citation (Macedonian): Јелена Лужина, „Презенција, игра, разлика“, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 169-186.